The child in charge: The case of child-participatory design of an environmental sustainability serious game - Vieira, S.; Alexandre, I. M.; Cardoso, E. (IDC '22: Interaction Design and Children, 2022)
In a technology-advanced world, it is known that children are growing up surrounded by electronic devices such as computers, mobile phones, and tablets, and eventually use them in their daily routines. Whereas the accessibility of these powerful tools is a long-standing issue, there is the need to conduct further studies including children during the design process. In this paper we explore a child-centred design approach through a serious game on sustainability. Participatory design, prototyping and evaluation are part of the process where we explore behaviour and feedback regarding the requested tasks. The preliminary results indicate that the children actively engaged with the prototypes, giving feedback and new ideas to make the serious game more engaging and easier for other children.